Matemática
Conta apagada
14

resolva as inequaçoes a seguir : 2x -2 > x+1 (x-4)/2 + (x-3)/3 < x-4 (x-4)/2 > x- 1/2

+1
(1) Respostas
danielefs16

2x -2 > x+1 2x -x > 1 +2 x > 3 S= {3}  (x-4)/2 + (x-3)/3 < x-4    mmc de 2 e 3= 6 [3.(x-4) + 2.(x-3) < 6.(x-4)]/6 [3x -12  + 2x -6 < 6x -24]/6   elimina o denominador 6 3x -12 + 2x -6 < 6x -24 3x +2x -6x < -24 +12 +6 5x -6x < -24 +18 -x < - 6.(-1) x > +6 S= {6} (x-4)/2 > x- 1/2     mmc=2 (x-4 > 2x -1)/2    elimina o denominador 2 x-4 > 2x -1 x -2x > -1 +4 -x > +4.(-1) +x < -4 S{-4}

Adicionar resposta